A carbon catalytic electrode material and its preparation method and application
Through a new method of preparing carbon material catalytic electrode materials, using work function to regulate sol and hydrothermal reactions, the problem of insufficient efficiency and selectivity of existing electrocatalytic technologies at low potentials is solved, high Faraday efficiency and mechanical stability are achieved, and the commercial application of electrocatalytic technology is promoted.
Patent Information
- Application Number
- CN202211440325.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-17
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-11-17
AI Technical Summary
The existing electrocatalytic technology is difficult to achieve high Faraday efficiency and selectivity at low potentials, and the mechanical stability is insufficient, which limits its commercial application.
A method for preparing carbon material catalytic electrode material is adopted to form a function-regulating sol through the mixing of non-ionic surfactant, silica sol, work-function control material, rare earth salt and aqueous ethanol solution, and a carbon material catalytic electrode material with high catalytic activity and mechanical strength is prepared through vacuum impregnation, hydrothermal reaction and hot extrusion molding.
High Faraday efficiency and selectivity are achieved at low potentials, which is specifically manifested as when CO2 reduction HCOOH is reduced, the current density can reach 11.9mA·cm-1, the Faraday efficiency HCOOH can reach 81.2%, FEH2 can reach 16.7%, and it also has high mechanical stability.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalytic electrode materials, and in particular to a carbon catalytic electrode material and a preparation method and application thereof. Background Art
[0002] With the continuous development and progress of human science and technology, energy and environment have become key issues that determine our sustainable future. The development of low-energy and high-efficiency material conversion technologies has become increasingly important. Electrocatalytic reaction technology is increasingly widely used in reactions involving water decomposition, renewable energy from artificial photosynthesis, or environmental management of chemical wastewater disposal due to its high energy efficiency, simple equipment manufacturing, and easy operation. The key to electrocatalytic technology lies in the design and development of catalytic electrodes. Among many electrocatalytic materials, carbon materials have become a very attractive catalyst carrier material due to their good stability, good electronic conductivity, and easy preparation of ideal porous structures. Carbon itself has no catalytic function. By doping the carbon source with heteroatoms, high-energy bonds are generated while forming carbon skeleton defects during the carbonization process. This not only allows the design of multi-level pores, hollows, or other special structures of high-performance carbon materials, but also improves the acidity and alkalinity, wettability, and activation energy of reactant or product molecules of carbon materials, and modulates their redox properties, thereby achieving catalytic performance.
[0003] At present, the methods used to prepare special structure carbon materials are mostly hydrothermal carbonization and template carbonization acid etching. However, the characteristics of these two processes determine that the carbon materials produced are mostly powdered or granular, which greatly limits their application in electrodes. There are two main existing electrode forming processes: one is the direct forming method, that is, the raw materials are directly mixed in a dry powder state, and then rolled into a film of a certain thickness by a film press, and then the film is composited with a conductive support substrate to form an electrode. The process equipment requirements of this direct forming method are too high, and its practical application has not been greatly improved; the other is a wet process, that is, various electrode powder raw materials are mixed with solvents, stirred to form a slurry, coated on a conductive support substrate, or directly hot-pressed with a thermoplastic binder. This wet process is the most common and mature, but this process requires acetylene black as a conductive agent when preparing the binder to reduce the coating of the binder on the carbon material. Although it can improve the problem of poor conductivity caused by the reduction of electrode density due to the introduction of the binder, this forming process is difficult to eliminate the decline in mechanical properties and catalytic properties caused by swelling. Therefore, developing a catalytic electrode with high Faradaic efficiency and selectivity and high mechanical stability at low potential has become a key technology to solve the lagging commercial application of electrocatalytic technology. Summary of the invention
[0004] The object of the present invention is to provide a carbon catalytic electrode material and a preparation method and application thereof. The carbon catalytic electrode material prepared by the method provided by the present invention has high Faraday efficiency (i.e. high activity) and high selectivity at low potential, and high mechanical stability.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a carbon catalytic electrode material, comprising the following steps:
[0007] (1) mixing a nonionic surfactant, a silica sol, a work function regulating material, a rare earth salt and an ethanol aqueous solution, adjusting the pH, adjusting the viscosity and allowing the mixture to stand in sequence to obtain a work function regulating sol;
[0008] (2) using a vacuum impregnation machine to impregnate the biomass powder into the work function regulating sol obtained in step (1), and then vacuum drying the impregnated biomass powder to obtain a biomass loaded material;
[0009] (3) mixing the biomass-loaded material obtained in step (2) with ethanol, water and aqueous ammonia, and then adding tetraethyl orthosilicate for a first dispersion to obtain a first dispersion liquid;
[0010] After adding a mixed solution containing phenolic substances, amine substances, pyrrole and ethanol to the first dispersion liquid, a second dispersion is performed to obtain a second dispersion liquid;
[0011] Adding formaldehyde solution to the second dispersion liquid to perform a third dispersion, and then sequentially performing solid-liquid separation, washing, drying and grinding to obtain an intermediate;
[0012] (4) mixing the intermediate obtained in step (3) with an alkaline solution, and then sequentially performing a hydrothermal reaction and freeze drying to obtain a carbon-enriched precursor;
[0013] (5) mixing the carbonized precursor obtained in step (4) with a binder, a transition metal, some elements of the third period, carbide and carboxymethyl cellulose, and then performing ball milling and hot extrusion molding in sequence to obtain a green body;
[0014] (6) The green body obtained in step (5) is sintered and etched in sequence to obtain a carbon catalytic electrode material.
[0015] Preferably, the work function regulating material in step (1) is one or more of nitrates, sulfates or hydrochlorides of Cs, Rb, Sm and Sr.
[0016] Preferably, in step (1), the viscosity is adjusted to 5-12 mPa·s.
[0017] Preferably, the vacuum degree of the immersion in step (2) is 0.050-0.12 MPa.
[0018] Preferably, the temperature of the hydrothermal reaction in step (4) is 110 to 190° C., and the time of the hydrothermal reaction is 5 to 11 hours.
[0019] Preferably, in step (5), the mass ratio of the carbonized precursor, the binder, the transition metal, some elements of the third period, the carbide, and the carboxymethyl cellulose is 5:(1-4):(0.1-0.5):(0.1-0.7):(0.05-0.6):(0.1-0.6).
[0020] Preferably, the temperature of the hot extrusion molding in step (5) is 150-200° C., the extrusion ratio of the hot extrusion molding is 8-22, the pressure of the hot extrusion molding is 25-55 MPa, and the time of the hot extrusion molding is 0.5-5 h.
[0021] Preferably, the step (6) is carried out by heating the sintering process in stages as follows: in the first stage, the temperature is raised from 24°C to 300-550°C at a rate of 2-6°C / min, and kept at this temperature for 3-18 min; in the second stage, the temperature is raised from 300-550°C to 600-1000°C at a rate of 18-22°C / min, and kept at this temperature for 50-80 min.
[0022] The present invention also provides a carbon catalytic electrode material prepared by the preparation method described in the above technical solution.
[0023] The present invention also provides a carbon catalytic electrode material prepared by the preparation method described in the above technical solution or the use of the carbon catalytic electrode material in the preparation of a material for converting electrical energy into chemical energy.
[0024] The present invention provides a method for preparing a carbon catalytic electrode material. First, a nonionic surfactant, a silica sol, a work function regulating material, a rare earth salt and an ethanol aqueous solution are used as raw materials to prepare a work function regulating sol. The work function regulating material is used as a raw material and the doping of rare earth atoms in the rare earth salt greatly increases the current density of the prepared carbon catalytic electrode, while inducing the formation of a local charge region, optimizing the adsorption characteristics of active intermediates on the interface, and promoting the coupling generation of carbon-carbon bonds (CC), thereby achieving selective regulation of the reaction products. In particular, in the catalytic CO2RR reaction, compared with the electrolytic decomposition of water to produce hydrogen reaction under low voltage conditions, electrons are more inclined to be transported to the active site of CO2 reduction; by adjusting the pH and coordinating the viscosity, the solution can be effectively decomposed. The invention solves the problems of blocked micropores, easy cracking and shedding of the work function regulating sol coating loaded on the surface of the biomass loaded material prepared subsequently, and promotes the adsorption and anchoring of the work function regulating sol on the biomass powder in the subsequent impregnation process by adjusting the viscosity, thereby increasing the specific surface area of the prepared carbon material catalytic electrode material and the bonding strength between the metal atoms and rare earth atoms (active centers) and the carbon material catalytic electrode material, thereby improving the reaction performance or activity of the finally prepared catalytic electrode, and the viscosity of the work function regulating sol is allowed to form a dynamic equilibrium by standing, and the formed sol will not agglomerate during the impregnation loading; the biomass powder is impregnated into the work function regulating sol by a vacuum impregnation machine to prepare the biomass loaded material, wherein the vacuum impregnation method can remove The gas adsorbed inside the pores of the porous biomass powder is conducive to the metal ions that need to be impregnated in the work function regulation sol to enter the pores of the biomass powder, and can especially promote the metal ions to alternately diffuse, embed and evenly distribute in the cell structure of the biomass powder in the cell cavity of the biomass powder, thereby inhibiting the agglomeration of metal atoms and rare earth atoms, reducing contact resistance, and accelerating electron transfer; then the biomass load material and ethyl orthosilicate are co-dispersed under alkaline conditions formed by ammonia water to form a sol, and finally a core-shell sol centered on the biomass load material is formed, and then a phenolic substance is added to react with formaldehyde to generate a third layer of a high molecular polymer with a core-shell structure; by adding amine substances and pyrrole, the biomass powder material can be During the hydrothermal reaction, carbonization forms pyrrole carbon catalytic active centers, further increasing nitrogen atom doping, producing more carbon skeleton defect sites, and improving catalytic performance; by slowly adding formaldehyde, high molecular polymers can be orderly grown on the sol shell to form a three-layer structure of biomass-silica sol-polymer, and phenols undergo electrophilic substitution with pyrrole and polymerization with formaldehyde to form phenolic polymers containing pyrrole side rings. Its special conjugation degree can effectively regulate the carbonization reaction process of the conjugated skeleton. While the shell directly constructs a developed pore structure, the side chain carbon formed can further selectively adsorb and desorb the reactants, greatly improving the catalytic efficiency of the electrocatalytic material; three dispersions, the first dispersion allows the biomass carrier and tetraethyl orthosilicate to be evenly dispersed in the solvent to form a homogeneous solution;The rate of the second dispersion is reduced, so that the silicon dioxide crystals generated by the hydrolysis of ethyl orthosilicate can grow in an orderly manner on the surface of the biomass carrier, forming a core-shell structure of silicon dioxide coated biomass; the third dispersion can make phenols and formaldehyde evenly dispersed and mixed, which is conducive to the uniform coating of phenolic polymers on the biomass-silicon dioxide core-shell, and through hydrothermal reaction and freeze drying, carbon microspheres with high purity, complete particle development, small particle size and uniform distribution, no agglomeration, good dispersibility, and controllable shape can be obtained, that is, carbonized precursors, and then the carbonized precursors are mixed with a binder, a transition metal, some elements of the third period, a carbide and carboxymethyl cellulose. After the synthesis, ball milling and hot extrusion molding are carried out in sequence to obtain a green body, so as to promote the embedding of metal on the carbon microspheres, i.e., the carbonized precursor, and the transition metal, some elements of the third period, carbides and carboxymethyl cellulose generate MAX phase during sintering, i.e., carbonization. A two-dimensional layered XMene material can be obtained on the surface of the MAX phase by etching. The special atomic structure and chemical bond characteristics of the MAX phase make the carbon material catalytic electrode material have the advantages of both metal and ceramic. The high mechanical strength and corrosion resistance can effectively reduce the instability of the electrochemical reactor caused by electrode swelling or corrosion collapse. In addition, the two-dimensional layered XMene structure has It has electrical properties similar to graphene, can affect the adsorption behavior of rare earth elements, can further synergistically promote the electrocatalytic efficiency, and finally after sintering, i.e., carbonization and etching, forms a core-shell structure with a metal-N doped carbon core with a low surface work function and a shell with a MAX semiconductor phase, so that the catalytic electrode material finally prepared produces a large current density (j) and a high Faraday efficiency (FE) at a low overpotential (η), and can ensure that the catalytic electrode material has enough active sites and a high specific surface area and high mechanical strength. Specifically, the core inside the core-shell structure, i.e., the small microspheres, have a low surface area. The work function forms a high catalytic carbon core, which can be used as a microreactor with a high reaction rate, and can prevent the direct contact between the catalytic carbon core and the electrolyte, greatly reducing the shedding of metal doping atoms and the occurrence of side reactions. The outer layer polymer inherits the topological structure of the phenolic-phenolic amine-pyrrole polymer to a certain extent during carbonization, especially the special conjugation degree of the phenolic-phenolic amine-pyrrole polymer, which can effectively regulate the carbonization reaction process of the conjugated skeleton. The side chain carbon formed while directly constructing a developed pore structure in the shell layer can further selectively adsorb and desorb the reactants, greatly improving the catalytic efficiency of the electrocatalytic material. The results of the embodiment show that when the carbon material catalytic electrode material prepared by the method provided by the present invention is used for electrocatalytic CO2 reduction to produce HCOOH, a large current density j of up to 11.9 mA cm is generated at a low overpotential η of -0.9 V; -1 , high Faraday efficiency FE HCOOH Up to 81.2%, FE H2 Up to 16.7%. DETAILED DESCRIPTION
[0025] The present invention provides a method for preparing a carbon catalytic electrode material, comprising the following steps:
[0026] (1) mixing a nonionic surfactant, a silica sol, a work function regulating material, a rare earth salt and an ethanol aqueous solution, adjusting the pH, adjusting the viscosity and allowing the mixture to stand in sequence to obtain a work function regulating sol;
[0027] (2) using a vacuum impregnation machine to impregnate the biomass powder into the work function regulating sol obtained in step (1), and then vacuum drying the impregnated biomass powder to obtain a biomass loaded material;
[0028] (3) mixing the biomass-loaded material obtained in step (2) with ethanol, water and aqueous ammonia, and then adding tetraethyl orthosilicate for a first dispersion to obtain a first dispersion liquid;
[0029] After adding a mixed solution containing phenolic substances, amine substances, pyrrole and ethanol to the first dispersion liquid, a second dispersion is performed to obtain a second dispersion liquid;
[0030] Adding formaldehyde solution to the second dispersion liquid to perform a third dispersion, and then sequentially performing solid-liquid separation, washing, drying and grinding to obtain an intermediate;
[0031] (4) mixing the intermediate obtained in step (3) with an alkaline solution, and then sequentially performing a hydrothermal reaction and freeze drying to obtain a carbon-enriched precursor;
[0032] (5) mixing the carbonized precursor obtained in step (4) with a binder, a transition metal, some elements of the third period, carbide and carboxymethyl cellulose, and then performing ball milling and hot extrusion molding in sequence to obtain a green body;
[0033] (6) The green body obtained in step (5) is sintered and etched in sequence to obtain a carbon catalytic electrode material.
[0034] In the present invention, unless otherwise specified, the raw materials used are conventional commercial products in the art.
[0035] The present invention mixes a nonionic surfactant, a silica sol, a work function regulating material, a rare earth salt and an ethanol aqueous solution, and then sequentially adjusts pH, adjusts viscosity and allows the mixture to stand to obtain a work function regulating sol.
[0036] The present invention has no particular limitation on the manner of mixing the nonionic surfactant, silica sol, work function regulating material, rare earth salt and ethanol aqueous solution, and it suffices to achieve uniform mixing of the components.
[0037] In the present invention, the nonionic surfactant is preferably one or more of citric acid, lactic acid, KH-550 and KH-570. The present invention utilizes the ability of nonionic surfactants to couple metal atoms and rare earth atoms, reduce the surface tension of the work function regulation sol, better infiltrate the surface of the biomass substrate, i.e., the biomass powder, and increase its loading rate on the work function regulation sol.
[0038] In the present invention, the content of SiO2 in the silica sol is preferably 15wt% to 55wt%, more preferably 20wt% to 50wt%. The content of SiO2 in the silica sol is controlled within the above range to ensure the cohesiveness of the work function-controlled sol, so that the Cs, Rb, Sm and Sr atoms in the work function-controlled sol are not easy to fall off during long-term charging and discharging.
[0039] In the present invention, the particle size of the silica sol is preferably 16 to 55 nm, more preferably 20 to 50 nm. The present invention controls the particle size of the silica sol within the above range to ensure that the work function-controlled sol can better break through the biomass cell wall in the biomass powder and anchor the metal atoms and rare earth atoms on the biomass powder skeleton.
[0040] In the present invention, the work function regulating material is preferably one or more of the nitrates, hydrochlorides or sulfates of Cs, Rb, Sm and Sr, and more preferably one or more of the nitrates of Cs, Rb, Sm and Sr. The present invention utilizes the work function regulating material to be filled into the biomass cells and intercellular spaces in the biomass powder after vacuum impregnation, and the polymer chains of the biomass are broken by pyrolysis and carbonization, and the carbon atoms and metal atoms are rearranged in order. The carbon skeleton structure can be rearranged, and the generated metal atom-O bonds, metal atom-C bonds, and metal atom-N bonds inject electrons into carbon atoms, reducing the escape work of electrons.
[0041] In the present invention, the rare earth salt is preferably one or more of the nitrates or sulfates of Ce, Pr, Y and La, and more preferably one or more of the nitrates of Ce, Pr, Y and La. The present invention utilizes rare earth materials to coordinate work function regulation, and the outermost electron complementation phenomenon can occur between Cs, Rb, Sm and Sr atoms in the sol through a quasi-superexchange effect, and coordinately inject electrons into the surrounding carbon atoms, so that the electrons in the carbon material catalytic electrode material are more easily transferred to the electrode surface, so that the Fermi level is closer to the vacuum level, and the activity of the carbon material catalytic electrode material is improved.
[0042] In the present invention, the volume concentration of ethanol in the ethanol aqueous solution is preferably 65% to 85%. In the present invention, the molar ratio of the nonionic surfactant, silica sol, work function regulating material, and rare earth salt is preferably 1: (1 to 9): (0.04 to 0.15): (0.08 to 0.15), and more preferably 1: (2 to 8): (0.06 to 0.1): (0.08 to 0.15). In the present invention, the molar ratio of the nonionic surfactant, silica sol, work function regulating material, and rare earth salt is controlled within the above range to ensure that a stable transparent sol system can be formed, that the colloid particles can slowly polymerize to form a gel with a three-dimensional spatial network structure, and that the components in the work function regulating sol are evenly distributed on the biomass powder, with good stability, and that the work function regulating sol coating obtained has a large specific surface area, a uniform pore size distribution, and high mechanical strength.
[0043] In the present invention, the adjusting agent used for adjusting the pH is preferably one or more of triethylamine, ethylenediamine, ethylamine, urea, and ammonia water. In the present invention, the adjusting pH is preferably adjusting the pH value of the mixed solution obtained by mixing a nonionic surfactant, a silica sol, a work function regulating material, a rare earth salt, and an ethanol aqueous solution to 7.3 to 9.5, more preferably 7.5 to 9. The present invention adjusts the pH value of the mixed solution obtained by mixing a nonionic surfactant, a silica sol, a work function regulating material, a rare earth salt, and an ethanol aqueous solution within the above range to ensure that the work function regulating sol has a higher Zeta potential, so that the work function regulating sol has better dispersibility and stability.
[0044] In the present invention, the viscosity is preferably adjusted to 4-14 mPa·S, more preferably 5-12 mPa·S after adjusting the pH. The present invention controls the hydrolysis rate of the silica sol by adjusting the viscosity to the above range, ensuring that the silica sol forms a uniform Si-O-Si chain structure during hydrolysis. 2- Ions combine to eventually form a three-dimensional SiO2 skeleton, which is then used to attach the work function-controlled sol to the biomass carrier. In the present invention, the viscosity adjustment method is preferably to evaporate and concentrate the mixed solution after pH adjustment or to add deionized water. In the present invention, the evaporation and concentration temperature is preferably 40°C to 60°C.
[0045] In the present invention, the standing time is preferably 5 to 13 hours, more preferably 6 to 12 hours. The present invention controls the standing time within the above range so that the work function regulates the viscosity of the sol to form a dynamic balance.
[0046] After obtaining the work function regulating sol, the present invention uses a vacuum impregnation machine to impregnate the biomass powder into the work function regulating sol, and then vacuum dries the impregnated biomass powder to obtain a biomass loaded material.
[0047] The present invention has no special limitation on the model of the vacuum impregnation machine, and any model commonly used in the art may be used.
[0048] In the present invention, the method for preparing the biomass powder preferably comprises the following steps:
[0049] (a) drying, crushing and screening the biomass in sequence to obtain pretreated biomass;
[0050] (b) vacuum drying the pretreated biomass obtained in step (a) to obtain biomass powder.
[0051] The present invention preferably sequentially dries, crushes and sieves the biomass to obtain the pretreated biomass.
[0052] In the present invention, the biomass is preferably one or more of mulberry branches, paulownia branches, pine branches, and bamboo.
[0053] The present invention has no particular limitation on the drying method, as long as the water in the biomass is removed.
[0054] The present invention has no particular limitation on the pulverizing method, and conventional technical solutions in the art may be used.
[0055] The present invention has no special limitation on the screening method, and conventional technical solutions in the art can be used. In the present invention, the particle size of the pretreated biomass is preferably 180 to 500 mesh, more preferably 200 to 400 mesh. The present invention controls the particle size of the pretreated biomass within the above range to ensure that the biomass powder prepared later can be completely carbonized by hydrothermal reaction and has a large catalytic specific surface area.
[0056] After obtaining the pretreated biomass, the present invention preferably performs vacuum drying on the pretreated biomass to obtain biomass powder.
[0057] In the present invention, the equipment used for vacuum drying is preferably a vacuum drying oven. In the present invention, the temperature of vacuum drying is preferably 70 to 130°C, more preferably 80 to 120°C; the time of vacuum drying is preferably 2 to 4 hours, more preferably 2 to 4 hours. The present invention controls the temperature and time of vacuum drying within the above ranges to achieve efficient and rapid drying and reduce production costs.
[0058] After vacuum drying is completed, the biomass powder obtained by vacuum drying is preferably sealed and stored in the present invention.
[0059] After obtaining the biomass powder, the present invention uses a vacuum impregnation machine to impregnate the biomass powder into the work function regulating sol, and then vacuum dries the impregnated biomass powder to obtain a biomass loaded material.
[0060] The present invention has no particular limitation on the amount of the work function regulating sol, as long as the amount of the work function regulating sol is sufficient to completely immerse the biomass powder.
[0061] In the present invention, the impregnation method is preferably to completely immerse the biomass powder into the work function regulating sol, and then maintain the vacuum negative pressure for 10-15 minutes.
[0062] In the present invention, the vacuum degree of the impregnation is preferably 0.040-0.14 MPa, more preferably 0.050-0.12 MPa. The present invention controls the vacuum degree of the impregnation within the above range to ensure that the active work function regulating sol can smoothly penetrate the biomass cell wall of the biomass powder and anchor the metal ions and rare earth ions inside the biomass powder material.
[0063] In the present invention, the total loading amount of the work function regulating sol in the biomass supported material is preferably 4wt% to 17wt%, more preferably 5wt% to 15wt%. The present invention controls the total loading amount of the work function regulating sol in the biomass supported material within the above range to reduce the surface work function energy of the prepared material catalytic electrode material.
[0064] In the present invention, when the total loading amount of the work function regulating sol in the biomass-loaded material is less than 4wt%, the present invention preferably repeats the operations of impregnating the biomass powder into the work function regulating sol and vacuum drying to ensure that the total loading amount of the work function regulating sol in the finally prepared biomass-loaded material is in the range of 4wt% to 17wt%.
[0065] In the present invention, the vacuum drying temperature is preferably 40 to 80°C, more preferably 60 to 70°C; the vacuum drying time is preferably 0.5 to 3 hours, more preferably 1 to 2.5 hours. The vacuum drying temperature and time are controlled within the above ranges to prevent the volatile substances in the biomass-loaded material from volatilizing too quickly during vacuum drying, resulting in the shedding of the surface work function-regulating sol layer.
[0066] After obtaining the biomass-loaded material, the present invention mixes the biomass-loaded material with ethanol, water and ammonia water, and then adds tetraethyl orthosilicate for first dispersion to obtain a first dispersion liquid.
[0067] The present invention has no particular limitation on the manner in which the biomass-loaded material is mixed with ethanol, water and aqueous ammonia, as long as each component is mixed evenly.
[0068] In the present invention, the volume ratio of ethanol, water and ammonia water is preferably (5-12): (2-7): 1, and more preferably (6-10): (3-5): 1. In the present invention, the volume ratio of ethanol, water and ammonia water is controlled within the above range to facilitate the hydrolysis of tetraethyl orthosilicate into silica microspheres.
[0069] In the present invention, the ratio of the volume of the ammonia water to the mass of the biomass support material is preferably (0.5-4) mL: 1 g, and more preferably (1-3) mL: 1 g. The present invention controls the ratio of the volume of the ammonia water to the mass of the biomass support material within the above range to facilitate the determination of the volumes of ethanol, water and ammonia water.
[0070] In the present invention, the mass ratio of the tetraethyl orthosilicate to the biomass support material is preferably (1-5): 1, more preferably 2-4: 1. The mass ratio of the tetraethyl orthosilicate to the biomass support material is controlled within the above range to ensure that the tetraethyl orthosilicate hydrolyzate can completely cover the surface of the biomass support material to form a core-shell structure.
[0071] In the present invention, the tetraethyl orthosilicate is preferably added under the condition of a dispersion with a rotation speed of 700 to 1500 r / min. In the present invention, the rotation speed of the first dispersion is preferably 700 to 1500 r / min, and more preferably 800 to 1400 r / min. In the present invention, the time of the first dispersion is preferably 20 to 40 min, and more preferably 25 to 35 min. The present invention controls the rotation speed and time of the first dispersion within the above range to facilitate the tetraethyl orthosilicate hydrolyzate to completely cover the surface of the biomass load material and ensure that the formed core-shell structure is uniform.
[0072] After obtaining the first dispersion, the present invention adds a mixed solution containing phenolic substances, amine substances, pyrrole and ethanol to the first dispersion, and then performs a second dispersion to obtain a second dispersion.
[0073] In the present invention, the molar ratio of phenolic substances, amine substances and pyrrole in the mixed solution containing phenolic substances, amine substances, pyrrole and ethanol is preferably 1: (0.5-2): (0.06-0.3), and more preferably 1: (1-1.5): (0.1-0.2). The present invention controls the molar ratio of phenolic substances, amine substances and pyrrole within the above range to ensure that there are enough N doping sites when the phenolic substances react with formaldehyde to generate phenolic polymer. In the present invention, the molar ratio of phenolic substances and tetraethyl orthosilicate is preferably (0.5-3): 1, and more preferably (1-2): 1. The present invention controls the molar ratio of phenolic substances and tetraethyl orthosilicate within the above range to ensure that the phenolic polymer generated by the reaction of phenolic substances and formaldehyde can completely cover the core-shell structure of the biomass and tetraethyl orthosilicate hydrolyzate to generate a three-layer core-shell structure.
[0074] In the present invention, the mixed solution containing phenolic substances, amine substances, pyrrole and ethanol is added under the condition of dispersion at a speed of 5 to 60 r / min. In the present invention, the phenolic substance is preferably one or more of phenol, hydroquinone and cardanol. In the present invention, the amine substance is preferably one or more of melamine, ethylenediamine, triethylenetetramine and dopamine. In the present invention, the rotation speed of the second dispersion is preferably 5 to 60 r / min, more preferably 10 to 50 r / min. In the present invention, the time of the second dispersion is preferably 50 to 70 min, more preferably 55 to 65 min. The present invention controls the rotation speed and time of the second dispersion within the above range to ensure that each substance can be evenly dispersed.
[0075] After obtaining the second dispersion, the present invention adds formaldehyde solution to the second dispersion to perform a third dispersion, and then sequentially performs solid-liquid separation, washing, drying and grinding to obtain an intermediate.
[0076] In the present invention, the volume concentration of formaldehyde in the formaldehyde solution is preferably 32% to 42%, more preferably 35% to 40%, and further preferably 37%. In the present invention, the ratio of the amount of formaldehyde to the amount of phenolic substances in the formaldehyde solution is preferably (0.6 to 1):1, and more preferably (0.8 to 1):1. The present invention controls the ratio of the amount of formaldehyde to the amount of phenolic substances within the above range to ensure that formaldehyde can react completely and prevent the presence of free formaldehyde in the generated third layer of high molecular polymer. In the present invention, the formaldehyde solution is preferably added within 20 to 140 minutes, and more preferably 30 to 120 minutes. In the present invention, the formaldehyde solution is preferably added under the condition of a dispersion with a rotation speed of 300 to 800 r / min. In the present invention, the rotation speed of the third dispersion is preferably 300 to 800 r / min, and more preferably 500 to 700 r / min. In the present invention, the time of the third dispersion is preferably 10 to 26 hours, and more preferably 12 to 24 hours.
[0077] The present invention controls the rotation speed and time of the third dispersion within the above range to prevent the formaldehyde from agglomerating due to excessively fast reaction rate with the phenolic substance, thereby ensuring that the generated polymer can grow in an orderly manner on the above two-layer core-shell.
[0078] In the present invention, the solid-liquid separation method is preferably centrifugation. In the present invention, the washing is preferably washing with water and ethanol.
[0079] In the present invention, the drying method is preferably vacuum drying. In the present invention, the vacuum drying temperature is preferably 50-70°C, more preferably 55-65°C; the vacuum drying time is preferably 10-14h, more preferably 11-13h.
[0080] In the present invention, the grinding method is preferably ball milling. In the present invention, the particle size of the intermediate is preferably 0.5 to 2.5 cm, more preferably 1 to 2 cm. The particle size of the intermediate is controlled within the above range in order to better adjust the mass ratio of the ceramic balls and the mixed raw materials.
[0081] After obtaining the intermediate, the present invention mixes the intermediate with an alkaline solution, and then sequentially performs a hydrothermal reaction and freeze-drying to obtain a carbon-enriched precursor.
[0082] In the present invention, the alkaline solution is preferably a potassium hydroxide aqueous solution; the molar concentration of the potassium hydroxide aqueous solution is preferably (0.06-1.5) mol / L, more preferably (0.1-1) mol / L.
[0083] The present invention has no particular limitation on the manner of mixing the intermediate and the alkaline solution, as long as the components are mixed uniformly.
[0084] In the present invention, the temperature of the hydrothermal reaction is preferably 100-200°C, more preferably 110-190°C, and the time of the hydrothermal reaction is preferably 4-12h, more preferably 5-11h. The temperature and time of the hydrothermal reaction are controlled within the above ranges to ensure that the intermediate can be completely hydrothermally carbonized into a three-layer core-shell structure.
[0085] In the present invention, the freeze-drying temperature is preferably -90 to -30°C, more preferably -80 to -40°C, and the freeze-drying time is preferably 22 to 26 hours, more preferably 23 to 24 hours.
[0086] After obtaining the carbonized precursor, the present invention mixes the carbonized precursor with a binder, a transition metal, some elements of the third period, carbide and carboxymethyl cellulose, and then performs ball milling and hot extrusion molding in sequence to obtain a green body.
[0087] In the present invention, the binder is preferably one or more of phenolic resin, thermoplastic polyurethane, epoxy resin. In the present invention, the transition metal is preferably one or more of Ti, Zn, Cu, Mn. In the present invention, the third period partial element is preferably one or more of Al, P, S, Si. In the present invention, the carbide is preferably one or both of silicon carbide and boron carbide.
[0088] The present invention has no special limitation on the manner of mixing the carbonized precursor with the binder, transition metal, some elements of the third period, carbide and carboxymethyl cellulose, as long as the components are mixed evenly.
[0089] In the present invention, the mass ratio of the carbon-rich precursor, the binder, the transition metal, the third periodic element, the carbide, and the carboxymethyl cellulose is preferably 5: (1-4): (0.1-0.5): (0.1-0.7): (0.05-0.6): (0.1-0.6), and more preferably 5: (2-3): (0.2-0.4): (0.2-0.6): (0.1-0.5): (0.2-0.5). The present invention controls the mass ratio of the carbon-rich precursor, the binder, the transition metal, the third periodic element, the carbide, and the carboxymethyl cellulose within the above range to facilitate hot pressing molding and more easily generate MAX phase during pyrolysis and carbonization.
[0090] In the present invention, the diameter of the ceramic balls used in the ball milling is preferably 1 cm; the mass ratio of the ceramic balls to the carbonized precursor, the binder, the transition metal, the third period part of the elements, the carbide, and the carboxymethyl cellulose to obtain the mixed raw material is preferably (45-90):1, and more preferably (50-80):1. The present invention controls the mass ratio of the ceramic balls to the mixed raw materials within the above range to ensure that the ground powder is at the micron level and increase the specific surface area. In the present invention, the rotation speed of the ball milling is preferably 200-600r / min, and more preferably 300-500r / min; the time of the ball milling is preferably 0.5-5h, and more preferably 1-4h. The present invention controls the rotation speed and time of the ball milling within the above range to cause deformation in the powder lattice, cause various dislocations and atomic defects, change its surface thermodynamic state, and increase the surface free energy.
[0091] In the present invention, the temperature of the hot extrusion molding is preferably 150-200°C, more preferably 155-195°C; the extrusion ratio of the hot extrusion molding is preferably 8-22, more preferably 9-20; the pressure of the hot extrusion molding is preferably 25-55MPa, more preferably 30-45MPa; the time of the hot extrusion molding is preferably 0.5-5h, more preferably 1-4h. The present invention controls the temperature, extrusion ratio, pressure and time of the hot extrusion molding within the above ranges so that the blank has good mechanical strength after molding.
[0092] After obtaining the green body, the present invention sequentially sintered and etched the green body to obtain a carbon catalytic electrode material.
[0093] In the present invention, the sintering is preferably carried out in an inert gas atmosphere; the inert gas is preferably argon or nitrogen; and the flow rate of the inert gas is preferably 100 to 200 mL / min.
[0094] In the present invention, the staged programmed temperature rise method of sintering is preferably: in the first stage, the temperature is raised from 24°C to 300-550°C at a rate of 2-6°C / min, and the temperature is kept for 3-18min; in the second stage, the temperature is raised from 300-550°C to 600-1000°C at a rate of 18-22°C / min, and the temperature is kept for 50-80min, and more preferably: in the first stage, the temperature is raised from 24°C to 350-500°C at a rate of 3-5°C / min, and the temperature is kept for 5-15min; in the second stage, the temperature is raised from 350-500°C to 650-900°C at a rate of 19-21°C / min, and the temperature is kept for 55-70min. The present invention adopts the above-mentioned staged programmed temperature rise method to ensure complete carbonization of the green body.
[0095] After the sintering is completed, the present invention preferably cools the sintered product naturally to room temperature.
[0096] After the natural cooling to room temperature is completed, the present invention preferably etches the product that has been naturally cooled to room temperature.
[0097] In the present invention, the etching reagent is preferably a NaOH aqueous solution with a molar concentration of 5 to 7 M or a HF aqueous solution with a volume concentration of 10 to 20%; the etching time is preferably 5 to 26 hours, more preferably 6 to 24 hours.
[0098] The carbon catalytic electrode material prepared by the method provided by the present invention has high activity and selectivity at low potential and high mechanical stability.
[0099] The present invention also provides a carbon catalytic electrode material prepared by the preparation method described in the above technical solution.
[0100] The carbon catalytic electrode material prepared by the method provided by the present invention has high activity and selectivity at low potential and high mechanical stability.
[0101] The present invention also provides a carbon catalytic electrode material prepared by the preparation method described in the above technical solution or the use of the carbon catalytic electrode material in preparing a material for converting electrical energy into chemical energy.
[0102] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0103] Example 1
[0104] The method for preparing a carbon catalytic electrode material comprises the following steps:
[0105] (1) 23.4 g KH-570, 60 g of 20 wt% silica sol with a particle size of 20 nm, 1.17 g cesium nitrate, and 3.47 g cerium nitrate were mixed and dissolved in 80 mL of 65% ethanol aqueous solution to obtain a mixed solution, urea was added to adjust the pH of the mixed solution to 7.5, and after continuing to stir for 20 min, the mixed solution was evaporated and concentrated at 40° C. to adjust the viscosity of the mixed solution after pH adjustment to 5 mPa·S, and then allowed to stand for 12 h to obtain a work function-controlled sol;
[0106] The molar ratio of KH-570 (i.e., nonionic surfactant), silica sol, cesium nitrate (i.e., work function regulating material), and cerium nitrate (i.e., rare earth salt) is 1:2:0.06:0.08;
[0107] (2) using a vacuum impregnation machine, impregnating 10 g of the biomass powder into 90 g of the work function-regulated sol obtained in step (1), setting the vacuum impregnation machine at a vacuum negative pressure of 0.98 MPa for 15 min, and then vacuum drying the impregnated biomass powder at 150° C. for 2 h to obtain a biomass-loaded material;
[0108] Repeat the impregnation operation of step (2) so that the total loading amount of the work function regulating sol in the biomass loading material finally prepared in step (2) reaches 15wt%;
[0109] The method for preparing the biomass powder comprises the following steps:
[0110] (a) drying, crushing and sieving 40 g of biomass paper mulberry branches in sequence to obtain pretreated biomass with a particle size of 200 mesh;
[0111] (b) placing the pretreated biomass obtained in step (a) into a vacuum drying oven and vacuum drying at 80° C. for 4 h to obtain 28 g of biomass powder;
[0112] (3) 10 g of the biomass support material obtained in step (2) was placed in a high-speed disperser containing a mixed solution of 100 mL of ethanol, 30 mL of water and 10 mL of ammonia water, 20 g of tetraethyl orthosilicate was added at a speed of 800 r / min, and then a first dispersion was performed at a speed of 800 r / min for 30 min to obtain a first dispersion liquid;
[0113] The volume ratio of ethanol, water and ammonia water is 10:3:1; the volume ratio of ammonia water to the mass ratio of biomass loading material is 1mL:1g; the mass ratio of tetraethyl orthosilicate to biomass loading material is 2:1.
[0114] Under the condition of a rotation speed of 10 r / min, a mixed solution containing 9 g of phenol, 14 g of triethylenetetramine, 0.65 g of pyrrole and 100 mL of ethanol was added to the first dispersion liquid, and then a second dispersion was performed under the condition of a rotation speed of 10 r / min for 60 min to obtain a second dispersion liquid;
[0115] The molar ratio of phenol (i.e. phenolic substance), triethylenetetramine (i.e. amine substance) and pyrrole is 1:1:0.1;
[0116] The molar ratio of the phenolic substance to tetraethyl orthosilicate is 1:1;
[0117] At a rotation speed of 10 r / min, 5.7 mL of 37 wt% formaldehyde solution was added to the second dispersion, and the formaldehyde solution was added within 30 min, and then a third dispersion was performed at a rotation speed of 500 r / min for 36 h, and then centrifuged, washed with water and ethanol, and dried in a vacuum oven at 60° C. for 12 h, and then ground into fine powder to obtain an intermediate with a particle size of 90 μm;
[0118] The molar ratio of formaldehyde to phenolic substances in the formaldehyde solution is 0.8:1;
[0119] (4) placing 50 g of the intermediate obtained in step (3) into a stainless steel autoclave, adding 10 mL of 0.1 mol / L KOH solution, performing a hydrothermal reaction at 120° C. for 6 h, then naturally cooling to room temperature, and freeze-drying at −40° C. for 24 h to obtain a carbonized precursor;
[0120] (5) 30 g of the carbonized precursor obtained in step (4) was mixed with 12 g of phenolic resin, 1.2 g of Ti powder, 1.2 g of Al powder, 0.6 g of silicon carbide powder, and 1.2 g of carboxymethyl cellulose, and then added to a ball mill containing 810 g of ceramic balls with a particle size of 1 cm. After ball milling for 1 h at a speed of 300 r / min, the mixture was moved into a hot pressing molding machine and hot extruded at a hot pressing temperature of 155° C., an extrusion ratio of 9, a pressure of 30 MPa, and a hot pressing time of 1 h to obtain a green body;
[0121] The mass ratio of the carbonized precursor, phenolic resin (i.e. binder), Ti powder (i.e. transition metal), Al powder (i.e. part of the third period elements), silicon carbide powder (i.e. carbide), and carboxymethyl cellulose is 5:2:0.2:0.2:0.1:0.2;
[0122] (6) placing the green body obtained in step (5) in a vacuum furnace for sintering under the protection of a nitrogen atmosphere, cooling naturally to room temperature after sintering, and then etching with a 5M NaOH aqueous solution for 6 hours to obtain a carbon catalytic electrode material;
[0123] The sintering temperature is programmed in stages: in the first stage, the temperature is increased from 24°C to 350°C at a rate of 3°C / min and kept at this temperature for 10 minutes; in the second stage, the temperature is increased from 350°C to 800°C at a rate of 20°C / min and kept at this temperature for 60 minutes.
[0124] Example 2
[0125] The method for preparing a carbon catalytic electrode material comprises the following steps:
[0126] (1) 22.1 g of KH-550, 96.1 g of 50 wt% silica sol with a particle size of 50 nm, 2.67 g of rubidium sulfate, and 6.1 g of yttrium sulfate were mixed and dissolved in 100 mL of 85% ethanol aqueous solution to obtain a mixed solution, urea was added to adjust the pH of the mixed solution to 9, and after continuing to stir for 20 min, the viscosity of the mixed solution after pH adjustment was adjusted to 12 mPa·S by evaporation and concentration at 60° C., and then allowed to stand for 6 h to obtain a work function-controlled sol;
[0127] The molar ratio of KH-550 (i.e., nonionic surfactant), silica sol, cesium nitrate (i.e., work function regulating material), and cerium nitrate (i.e., rare earth salt) is 1:8:0.1:0.1;
[0128] (2) using a vacuum impregnation machine, impregnating 10 g of biomass powder into 150 g of the work function-regulated sol obtained in step (1), setting the vacuum impregnation machine to a vacuum negative pressure of 0.065 MPa for 10 min, and then vacuum drying the impregnated biomass powder at 100 ° C for 1 h to obtain a biomass-loaded material;
[0129] Repeat the impregnation operation of step (2) so that the total loading amount of the work function regulating sol in the biomass loading material finally prepared in step (2) reaches 5 wt%;
[0130] The method for preparing the biomass powder comprises the following steps:
[0131] (a) drying, crushing and sieving 40 g of paulownia branches and trunks in sequence to obtain pretreated biomass with a particle size of 400 mesh;
[0132] (b) placing the pretreated biomass obtained in step (a) into a vacuum drying oven and vacuum drying at 120° C. for 2 h to obtain 20 g of biomass powder;
[0133] (3) 10 g of the biomass support material obtained in step (2) was placed in a high-speed disperser containing a mixed solution of 180 mL of ethanol, 150 mL of water and 30 mL of ammonia water, 40 g of tetraethyl orthosilicate was added at a speed of 1400 r / min, and then a first dispersion was performed at a speed of 1400 r / min for 30 min to obtain a first dispersion liquid;
[0134] The volume ratio of ethanol, water and ammonia water is 6:5:1; the volume ratio of ammonia water to the mass ratio of biomass loading material is 3mL:1g; the mass ratio of tetraethyl orthosilicate to biomass loading material is 4:1.
[0135] At a rotation speed of 50 r / min, a mixed solution containing 42.3 g of hydroquinone, 72.7 g of melamine, 5.1 g of pyrrole and 100 mL of ethanol was added to the first dispersion, and then a second dispersion was performed at a rotation speed of 50 r / min for 60 min to obtain a second dispersion;
[0136] The molar ratio of phenol (i.e. phenolic substance), triethylenetetramine (i.e. amine substance) and pyrrole is 1:1.5:0.2;
[0137] The molar ratio of the phenolic substance to tetraethyl orthosilicate is 2:1;
[0138] At a speed of 50 r / min, 28.9 mL of 37 wt% formaldehyde solution was added to the second dispersion, and the formaldehyde solution was added within 120 min. Then, a third dispersion was performed at a speed of 800 r / min for 36 h, and then centrifuged, washed with water and ethanol, and dried in a vacuum oven at 60° C. for 12 h, and then ground into fine powder to obtain an intermediate with a particle size of 90 μm.
[0139] The molar ratio of formaldehyde to phenolic substances in the formaldehyde solution is 1:1;
[0140] (4) 50 g of the intermediate obtained in step (3) was placed in a stainless steel autoclave, 10 mL of 1 mol / L KOH solution was added, and a hydrothermal reaction was carried out at 170° C. for 10 h, then naturally cooled to room temperature, and freeze-dried at -80° C. for 24 h to obtain a carbonized precursor;
[0141] (5) 30 g of the carbonized precursor obtained in step (4) was mixed with 18 g of phenolic resin, 2.4 g of Zn powder, 2.4 g of P powder, 3 g of boron carbide powder, and 3 g of carboxymethyl cellulose, and then added to a ball mill containing 2304 g of ceramic balls with a particle size of 1 cm. The mixture was ball milled at a speed of 500 r / min for 4 h, and then moved into a hot pressing molding machine for hot extrusion molding at a hot pressing temperature of 195° C., an extrusion ratio of 20, a pressure of 45 MPa, and a hot pressing time of 4 h to obtain a green body;
[0142] The mass ratio of the carbonized precursor, phenolic resin (i.e., binder), Zn powder (i.e., transition metal), P powder (i.e., some elements of the third period), boron carbide powder (i.e., carbide), and carboxymethyl cellulose is 5:3:0.4:0.4:0.5:0.5;
[0143] (6) placing the green body obtained in step (5) in a vacuum furnace for sintering under the protection of a nitrogen atmosphere, cooling naturally to room temperature after sintering, and then etching with a 7M NaOH aqueous solution for 6 hours to obtain a carbon catalytic electrode material;
[0144] The sintering temperature is programmed in stages: in the first stage, the temperature is increased from 24°C to 350°C at a rate of 5°C / min and kept at this temperature for 15 minutes; in the second stage, the temperature is increased from 350°C to 900°C at a rate of 20°C / min and kept at this temperature for 120 minutes.
[0145] Example 3
[0146] The method for preparing a carbon catalytic electrode material comprises the following steps:
[0147] (1) 19.2 g of citric acid, 80.1 g of 30 wt% silica sol with a particle size of 30 nm, 1.49 g of samarium nitrate, and 2.02 g of praseodymium nitrate were mixed and dissolved in 100 mL of 70% ethanol aqueous solution to obtain a mixed solution, urea was added to adjust the pH of the mixed solution to 8, and the mixture was stirred for 20 min. The mixture was concentrated by evaporation at 45° C. to adjust the viscosity of the mixed solution after pH adjustment to 8 mPa·S, and then allowed to stand for 7 h to obtain a work function-controlled sol;
[0148] The molar ratio of the citric acid (i.e., nonionic surfactant), silica sol, samarium nitrate (i.e., work function regulating material), and praseodymium nitrate (i.e., rare earth salt) is 1:4:0.07:0.1;
[0149] (2) using a vacuum impregnation machine, impregnating 10 g of the biomass powder into 100 g of the work function-regulated sol obtained in step (1), setting the vacuum impregnation machine at a vacuum negative pressure of 0.48 MPa for 12 min, and then vacuum drying the impregnated biomass powder at 120° C. for 1.2 h to obtain a biomass-loaded material;
[0150] Repeat the impregnation operation of step (2) so that the total loading amount of the work function regulating sol in the biomass loading material finally prepared in step (2) reaches 10wt%;
[0151] The method for preparing the biomass powder comprises the following steps:
[0152] (a) drying, crushing and sieving 40 g of biomass pine branches in sequence to obtain pretreated biomass with a particle size of 250 mesh;
[0153] (b) placing the pretreated biomass obtained in step (a) into a vacuum drying oven and vacuum drying at 90° C. for 3 h to obtain 28 g of biomass powder;
[0154] (3) 10 g of the biomass support material obtained in step (2) was placed in a high-speed disperser containing a mixed solution of 105 mL of ethanol, 60 mL of water and 15 mL of ammonia water, 25 g of tetraethyl orthosilicate was added at a speed of 1000 r / min, and then a first dispersion was performed at a speed of 1000 r / min for 30 min to obtain a first dispersion liquid;
[0155] The volume ratio of ethanol, water and ammonia water is 7:4:1; the volume ratio of ammonia water to the mass ratio of biomass loading material is 1.5mL:1g; the mass ratio of tetraethyl orthosilicate to biomass loading material is 2.5:1.
[0156] At a rotation speed of 10 r / min, a mixed solution containing 16.9 g of phenol, 10.8 g of ethylenediamine, 1.2 g of pyrrole and 100 mL of ethanol was added to the first dispersion, and then a second dispersion was performed at a rotation speed of 20 r / min for 60 min to obtain a second dispersion;
[0157] The molar ratio of the phenol (i.e., phenolic substance), triethylenetetramine (i.e., amine substance) and pyrrole is preferably 1:1:0.1;
[0158] The molar ratio of the phenolic substance to tetraethyl orthosilicate is 1.5:1;
[0159] At a speed of 20 r / min, 11.5 mL of 37 wt% formaldehyde solution was added to the second dispersion liquid, and the formaldehyde solution was added within 50 min, and then a third dispersion was performed at a speed of 600 r / min for 18 h, and then centrifuged, washed with water and ethanol, and dried in a vacuum oven at 60° C. for 12 h, and then ground into fine powder to obtain an intermediate with a particle size of 90 μm;
[0160] The molar ratio of formaldehyde to phenolic substances in the formaldehyde solution is 0.85:1;
[0161] (4) 50 g of the intermediate obtained in step (3) was placed in a stainless steel autoclave, 10 mL of 0.5 mol / L KOH solution was added, and a hydrothermal reaction was carried out at 150° C. for 8 h, then naturally cooled to room temperature, and freeze-dried at -70° C. for 24 h to obtain a carbonized precursor;
[0162] (5) 30 g of the carbonized precursor obtained in step (4) was mixed with 15 g of phenolic resin, 1.8 g of Cu powder, 1.2 g of S powder, 0.6 g of silicon carbide powder, and 1.2 g of carboxymethyl cellulose, and then added to a ball mill containing 1188 g of ceramic balls with a particle size of 1 cm. The mixture was ball milled at a speed of 350 r / min for 2 h, and then transferred to a hot pressing molding machine for hot extrusion molding at a hot pressing temperature of 170° C., an extrusion ratio of 12, a pressure of 35 MPa, and a hot pressing time of 2 h to obtain a green body;
[0163] The mass ratio of the carbonized precursor, phenolic resin (i.e., binder), Cu powder (i.e., transition metal), S powder (i.e., some elements of the third period), silicon carbide powder (i.e., carbide), and carboxymethyl cellulose is 5:2.5:0.3:0.2:0.1:0.2;
[0164] (6) placing the green body obtained in step (5) in a vacuum furnace for sintering under the protection of a nitrogen atmosphere, cooling naturally to room temperature after sintering, and then etching with a 10% by volume HF solution for 6 hours to obtain a carbon catalytic electrode material;
[0165] The sintering temperature is programmed in stages: in the first stage, the temperature is increased from 24°C to 350°C at a rate of 3°C / min and kept at this temperature for 10 minutes; in the second stage, the temperature is increased from 350°C to 800°C at a rate of 20°C / min and kept at this temperature for 60 minutes.
[0166] Example 4
[0167] The method for preparing a carbon catalytic electrode material comprises the following steps:
[0168] (1) 18.2 g of lactic acid, 90.1 g of 40 wt% silica sol with a particle size of 40 nm, 1.9 g of strontium nitrate and 5.2 g of lanthanum nitrate were mixed and dissolved in an ethanol aqueous solution with a volume fraction of 80% to obtain a mixed solution, urea was added to adjust the pH of the mixed solution to 8, and the mixture was stirred for 20 min. After that, the mixture was stirred for 20 min, and the viscosity of the mixed solution after the pH adjustment was adjusted to 5 mPa·S with deionized water, and then the mixture was allowed to stand for 12 h to obtain a work function control sol;
[0169] The molar ratio of the lactic acid (i.e., non-ionic surfactant), silica sol, strontium nitrate (i.e., work function regulating material), and lanthanum nitrate (i.e., rare earth salt) is 1:6:0.07:0.12;
[0170] (2) using a vacuum impregnation machine, impregnating 10 g of the biomass powder into 120 g of the work function-regulated sol obtained in step (1), setting the vacuum impregnation machine to a vacuum negative pressure of 0.89 MPa for 12 min, and then vacuum drying the impregnated biomass powder at 150° C. for 1 h to obtain a biomass-loaded material;
[0171] Repeat the impregnation operation of step (2) so that the total loading amount of the work function regulating sol in the biomass loading material finally prepared in step (2) reaches 12 wt %;
[0172] The method for preparing the biomass powder comprises the following steps:
[0173] (a) drying, crushing and sieving 40 g of biomass bamboo in sequence to obtain pretreated biomass with a particle size of 350 mesh;
[0174] (b) placing the pretreated biomass obtained in step (a) into a vacuum drying oven and vacuum drying at 120° C. for 4 h to obtain 28 g of biomass powder;
[0175] (3) 10 g of the biomass support material obtained in step (2) was placed in a high-speed disperser containing a mixed solution of 225 mL of ethanol, 125 mL of water and 25 mL of ammonia water, 35 g of tetraethyl orthosilicate was added at a speed of 1200 r / min, and then a first dispersion was performed at a speed of 1200 r / min for 30 min to obtain a first dispersion liquid;
[0176] The volume ratio of ethanol, water and ammonia water is 9:5:1; the volume ratio of ammonia water to the mass ratio of biomass loading material is 2.5mL:1g; the mass ratio of tetraethyl orthosilicate to biomass loading material is 3.5:1.
[0177] At a rotation speed of 40 r / min, a mixed solution containing 31.6 g of phenol, 63.6 g of melamine, 4.51 g of pyrrole and 100 mL of ethanol was added to the first dispersion, and then a second dispersion was performed at a rotation speed of 40 r / min for 60 min to obtain a second dispersion;
[0178] The molar ratio of the phenol (i.e., phenolic substance), dopamine (i.e., amine substance) and pyrrole is preferably 1:1.5:0.2;
[0179] The molar ratio of the phenolic substance to tetraethyl orthosilicate is 2:1;
[0180] At a speed of 40 r / min, 24 mL of 37 wt% formaldehyde solution was added to the second dispersion, and the formaldehyde solution was added within 50 min, and then a third dispersion was performed at a speed of 700 r / min for 24 h, and then centrifuged, washed with water and ethanol, and dried in a vacuum oven at 60° C. for 12 h, and then ground into fine powder to obtain an intermediate with a particle size of 90 μm;
[0181] The molar ratio of formaldehyde to phenolic substances in the formaldehyde solution is 0.95:1;
[0182] (4) 50 g of the intermediate obtained in step (3) was placed in a stainless steel autoclave, 10 mL of 0.8 mol / L KOH solution was added, and a hydrothermal reaction was carried out at 120° C. for 9 h, then naturally cooled to room temperature, and freeze-dried at -60° C. for 24 h to obtain a carbonized precursor;
[0183] (5) 30 g of the carbonized precursor obtained in step (4) was mixed with 12 g of phenolic resin, 1.8 g of Mn powder, 1.8 g of Si powder, 2.4 g of silicon carbide boron, and 1.8 g of carboxymethyl cellulose, and then added to a ball mill containing 1386 g of ceramic balls with a particle size of 1 cm. The mixture was ball milled at a speed of 450 r / min for 3 h, and then moved into a hot pressing molding machine for hot extrusion molding at a hot pressing temperature of 180° C., an extrusion ratio of 17, a pressure of 40 MPa, and a hot pressing time of 3 h to obtain a green body;
[0184] The mass ratio of the carbonized precursor, phenolic resin (i.e. binder), Ti powder (i.e. transition metal), Al powder (i.e. some elements of the third period), silicon carbide powder (i.e. carbide), and carboxymethyl cellulose is 5:2:0.3:0.3:0.4:0.3;
[0185] (6) placing the green body obtained in step (5) in a vacuum furnace under the protection of an argon atmosphere for sintering, cooling naturally to room temperature after sintering, and then etching with HF having a volume concentration of 20% for 12 hours to obtain a carbon catalytic electrode material;
[0186] The sintering temperature is programmed in stages: in the first stage, the temperature is increased from 24°C to 350°C at a rate of 5°C / min and kept at this temperature for 15 minutes; in the second stage, the temperature is increased from 350°C to 900°C at a rate of 20°C / min and kept at this temperature for 120 minutes.
[0187] The carbon catalytic electrode materials prepared in Examples 1 to 4 were respectively subjected to electrocatalytic CO2 reduction (CO2 reduction reaction, CO2RR) to produce HCOOH performance tests.
[0188] The test method is as follows: a three-electrode H-type electrolytic cell (the counter electrode is a Pt sheet electrode, and the reference electrode is an Ag / AgCl electrode) is connected to a CHI 760E electrochemical workstation, and a KHCO3 solution saturated with CO2 and having a concentration of 0.1 mol / L is injected as an electrolyte to test the CO2RR activity of the carbon catalytic electrode material; first, in the test voltage range of 0 to -1.2 V (vs. RHE), the CO2RR activity of the carbon catalytic electrode material is measured at 50 mV·s -1 The rate scan was performed, and the activated sample was tested by continuous cyclic voltammetry (CV). After obtaining a stable CV curve, the catalytic electrode materials prepared in Examples 1 to 4 were tested by linear sweep voltammetry (LSV) at the same test voltage. The Faraday current efficiency (FE) was calculated by the formula FE = (m×n×F) / (I×t)×100%, where m is the actual molar number of the product, n is the number of reaction electrons, F is the Faraday constant, that is, the number of charges contained in an electron, I is the current, and t is the time. The carbon catalytic electrode materials prepared in Examples 1 to 4 were tested to produce a large current density j at a low overpotential η of -9V. The specific results are shown in Table 1.
[0189] In Table 1, FE HCOOH Represents the Faradaic current efficiency of formic acid production; FE H2 Represents the Faraday current efficiency of hydrogen production; FE 其他产物 Represents the Faradaic current efficiency of other products;
[0190] Table 1 Performance test results of carbon catalytic electrode materials prepared in Examples 1 to 4
[0191] Test items Example 1 Example 2 Example 3 Example 4 Current density <![CDATA[11.9mA·cm -1 ]]> <![CDATA[11.7mA·cm -1 ]]> <![CDATA[11.9mA·cm -1 ]]> <![CDATA[11.8mA·cm -1 ]]> <![CDATA[FE HCOOH ]]> 81.2% 80.7% 81.0% 80.9% <![CDATA[FE H2 ]]> 16.5% 16.7% 16.7% 16.6% <![CDATA[FE 其他产物 ]]> 2.3% 2.6% 2.3% 2.5%
[0192] In summary, when the carbon catalytic electrode material prepared by the method provided by the present invention is used for electrocatalytic reduction of CO2 to produce HCOOH, a large current density j of up to 11.9 mA cm is generated at a low overpotential η of -9 V. -1, high Faraday efficiency FE HCOOH Up to 81.2%, FE H2 Up to 16.7%.
[0193] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a carbon catalytic electrode material, comprising the following steps: (1) mixing a nonionic surfactant, a silica sol, a work function regulating material, a rare earth salt and an ethanol aqueous solution, adjusting the pH, adjusting the viscosity and allowing the mixture to stand in sequence to obtain a work function regulating sol; (2) using a vacuum impregnation machine to impregnate the biomass powder into the work function regulating sol obtained in step (1), and then vacuum drying the impregnated biomass powder to obtain a biomass loaded material; (3) mixing the biomass-loaded material obtained in step (2) with ethanol, water and ammonia water, and then adding tetraethyl orthosilicate for a first dispersion to obtain a first dispersion; adding a mixed solution containing phenolic substances, amine substances, pyrrole and ethanol to the first dispersion, and then performing a second dispersion to obtain a second dispersion; adding a formaldehyde solution to the second dispersion, and performing a third dispersion, and then sequentially performing solid-liquid separation, washing, drying and grinding to obtain an intermediate; (4) mixing the intermediate obtained in step (3) with an alkaline solution, and then sequentially performing a hydrothermal reaction and freeze drying to obtain a carbon-enriched precursor; (5) mixing the carbonized precursor obtained in step (4) with a binder, a transition metal, some elements of the third period, carbide and carboxymethyl cellulose, and then performing ball milling and hot extrusion molding in sequence to obtain a green body; (6) sintering and etching the green body obtained in step (5) in sequence to obtain a carbon catalytic electrode material; The work function regulating material in step (1) is one or more of nitrates, sulfates or hydrochlorides of Cs, Sm and Sr; The rare earth salt in step (1) is one or more of nitrates or sulfates of Ce, Pr and La; The transition metal in step (5) is one or more of Ti, Zn and Cu; In step (5), the third periodic element is one or more of Al, P and S; The carbide in step (5) is one or both of silicon carbide and boron carbide.
2. The preparation method according to claim 1, characterized in that: In the step (1), the viscosity is adjusted to 5-12 mPa·s.
3. The preparation method according to claim 1, characterized in that: The vacuum degree of the immersion in the step (2) is 0.050-0.12 MPa.
4. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (4) is 110 to 190° C., and the time of the hydrothermal reaction is 5 to 11 hours.
5. The preparation method according to claim 1, characterized in that: In the step (5), the mass ratio of the carbonized precursor, the binder, the transition metal, some elements of the third period, the carbide, and the carboxymethyl cellulose is 5:(1-4):(0.1-0.5):(0.1-0.7):(0.05-0.6):(0.1-0.6).
6. The preparation method according to claim 1, characterized in that: The temperature of the hot extrusion molding in the step (5) is 150-200° C., the extrusion ratio of the hot extrusion molding is 8-22, the pressure of the hot extrusion molding is 25-55 MPa, and the time of the hot extrusion molding is 0.5-5 h.
7. The preparation method according to claim 1, characterized in that: The sintering in step (6) is carried out in stages by programmed heating: in the first stage, the temperature is raised from 24°C to 300-550°C at a rate of 2-6°C / min, and kept at this temperature for 3-18 minutes; in the second stage, the temperature is raised from 300-550°C to 600-1000°C at a rate of 18-22°C / min, and kept at this temperature for 50-80 minutes.
8. The carbon catalytic electrode material prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the carbon catalytic electrode material according to claim 8 in electrocatalytic reduction of CO2 to produce HCOOH / H2.
Citation Information
Patent Citations
Copper-doped bismuth bimetallic material as well as preparation and application thereof
CN111501060A
Preparation method and application of indium-based catalyst for preparing low-carbon alcohol through electrocatalytic reduction of CO2
CN113373471A